The evaluation of learning in e-learning, some reflections (Revista Electrónica Calidad en la Educación Superior, 2021)
In the current context where the 2020 Covid-19 pandemic has permeated all educational systems worldwide, the gaze has been turned to distance education and e-learning as a viable option to maintain training processes in schools. different levels. The evaluation of learning is a subject of great importance to obtain the best use of virtual learning environments, which implies knowing some conceptual details for decision-making in terms of mediation and strategies that can be carried out. This article is based on the theoretical review that supports a doctoral research, which aims to deepen on this issue in the context of the State Distance University of Costa Rica at the level of two study plans. The objective of this article is to analyze the main contributions of the subject of the evaluation of learning in e-learning. Among the most important aspects of the findings are the importance of the formative dimension of learning evaluation, as well as the need for student involvement in evaluation through collaborative learning strategies, all of this tending to promote self-regulation. and the competence of learning to learn.
Keywords: evaluation of learning; e-learning; distance education; collaborative work